1991
DOI: 10.1152/jappl.1991.70.5.2268
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid and thyrotropin-releasing hormone effects on preterm sheep lung function

Abstract: Four groups of twin sheep fetuses were catheterized at 121 days of gestational age and intravenously infused with saline, 0.75 mg.kg-1.h-1 cortisol for 60 h, five intermittent bolus injections of 5 micrograms/kg thyrotropin-releasing hormone (TRH) at 12-h intervals, or both hormones before delivery at 128 days. At birth, the lambs were randomized to receive surfactant or no treatment. Surfactant treatment improved lung function of all the groups. Corticosteroids alone and in combination with TRH improved compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 34 publications
3
33
0
1
Order By: Relevance
“…As wa s seen for the ca rdiov ascular effects, it is po ssible that a low er dos e of T 4 may hav e augmented the FFA responses as had been anticipated. Th e results of the thyroid hormone assa ys demonstrate that anten atal BETA exp osure augments fet al umbilical and postnatal circulating T3 level s. The mechanism for this effect is presumed to be induction of the hepatic monodeiodinase activity responsible for T 4 to T 3 conversion (8,42). The dose of T 4 we used in combination with BETA in the present study blunted both the prenatal and postnatal increase in T 3 , presum ably via suppress ion of thyroidal T 4 secretion.…”
Section: Ol---lij-----------------supporting
confidence: 49%
“…As wa s seen for the ca rdiov ascular effects, it is po ssible that a low er dos e of T 4 may hav e augmented the FFA responses as had been anticipated. Th e results of the thyroid hormone assa ys demonstrate that anten atal BETA exp osure augments fet al umbilical and postnatal circulating T3 level s. The mechanism for this effect is presumed to be induction of the hepatic monodeiodinase activity responsible for T 4 to T 3 conversion (8,42). The dose of T 4 we used in combination with BETA in the present study blunted both the prenatal and postnatal increase in T 3 , presum ably via suppress ion of thyroidal T 4 secretion.…”
Section: Ol---lij-----------------supporting
confidence: 49%
“…The observation by Ikegami et al (17) that prenatal corticosteroids improve lung function measures without changing surfactant pool sizes and our finding that corticosteroids induce an increase in catalase activity raise the issue of cause and effect. The induction of lung catalase activity by corticosteroids and the catalase activity of natural surfactant both have the potential to reduce pulmonary oxygen toxicity.…”
Section: Discussionmentioning
confidence: 59%
“…Animals used in this study were the sheep used for lung function studies reported by Ikegami et al (17). In brief, date-mated mixed Western breed sheep with twin pregnancies underwent hysterotomy at 121 + 1 d gestation (term is 150 d).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ment may lead to delays in maturation of the brain (Chan and Kilby, 2000), the lung (Ikegami et al, 1991;Hume et al, 2001) and the skeletal muscles (Hausman and Watson, 1994). In altricial species characterised by low body maturity at birth, such as the rabbit, the hypothalamo-pituitary-thyroid axis (HPTA) develops after birth (Mach, 1977), and the thyroid hormones of maternal origin are detectable in fetuses long before the onset of fetal thyroid function (Obregon et al, 1984;Escobar del Rey et al, 1986).…”
mentioning
confidence: 99%